PENGARUH LITERASI MEDIA DIGITAL TERHADAP PRESTASI BELAJAR MAHASISWA (Prodi PAI UNIKS) - Fernanda Effendi; Bustanur Bustanur; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research is motivated by the development of digital media and its use in the learning process in both elementary and secondary schools and higher education. In the Islamic Education Department at Universitas Islam Kuantan Singingi, students are very active in using digital media related to the learning process. But on the other hand students are not selective, do not have special rules in accessing digital media, even do not trust the material accessed through digital media. Based on the phenomenon above, this study aims to determine whether there is an effect of digital media literacy on the learning achievement of students of the Islamic Education Department at Universitas Islam Kuantan Singingi. This research is quantitative with causal associative explanation levels, which is carried out in the Islamic Education Department, Universitas Islam Kuantan Singingi. The data is collected by a questionnaire whose indicators are taken from publications EAVI (European Association for Viewers Internets) entitled Study on Assessment Criteria for Media Literacy Levels, interviews, observation, and documentation. Data analysis using the Chi-Square formula which is processed by SPSS 17.0 software. The results showed that there was no positive and significant effect or influence of digital media literacy toward the student achievement in the Islamic Education Department at the Universitas Islam Kuantan Singingi, which is the Chi-Square’s value is 2,431; smaller than the Chi-Square’s table value is 7,815. Kata Kunci: literasi media digital; prestasi belajar